Safety and immunogenicity of a new Sabin inactivated poliovirus vaccine candidate produced on the PER.C6® cell-line: a phase 1 randomized controlled trial in adults - Isabel Leroux-Roels; Geert Leroux-Roels; Georgi Shukarev; Hanneke Schuitemaker; Conor Cahill; Richard de Rooij; Martin Struijs; Hester van Zeeburg; Jeanne-Marie Jacquet (Taylor & Francis Group, 2021)
This first-in-human study (NCT03032588), conducted in Belgium, evaluated a new inactivated poliovirus vaccines (IPV) candidate based on Sabin poliovirus strains grown on the high-yield PER.C6® cell line. Healthy adults (N = 32) were randomized (1:1) to receive a single dose of PER.C6-based Sabin-IPV (sIPV, 15:35:112.5 DU/dose) or conventional Salk-IPV (cIPV, 40:8:32 DU/dose). Reactogenicity was assessed up to 7 days after vaccination, immunogenicity 28 days after vaccination, and safety up to 6 months after vaccination. Solicited adverse events (AEs) were mild to moderate, no changes of concern in vital signs or safety laboratory values were observed, and no severe AEs (SAEs) or vaccine-related unsolicited AEs were reported after vaccination. A trend to more frequent solicited AEs after sIPV than after cIPV administration was observed. Most participants had preexisting neutralizing antibodies against poliovirus types (titer ≥8), which were strongly boosted by sIPV. Post-vaccination geometric mean titers were high (≥12,000) and similar across the two vaccination groups. Only participants with very high preexisting antibody levels did not show a vaccine-induced response, defined in seropositive participants as a 4-fold titer increase. The 10 initially seronegative (titer <8) participants (n = 5 in each study group) seroconverted and all participants had seroprotective antibody levels post-vaccination. The antibodies elicited by sIPV neutralized both Sabin and Salk poliovirus strains. In conclusion, the PER.C6®-based sIPV was well tolerated and highly immunogenic in adults with preexisting antibodies to poliovirus.